Dark energy and the BOOMERANG data - Amendola, Luca (Physical review letters, 2001)
The recent high-quality BOOMERANG data allow the testing of many competing cosmological models. Here I present a seven-parameter likelihood analysis of dark energy models with exponential potential and explicit coupling to dark matter. The BOOMERANG data constrain the dimensionless coupling β to be smaller than 0.1, an order of magnitude better than previous limits. In terms of the constant ξ of nonminimally coupled theories, this amounts to ξ<0.01. On the other hand, BOOMERANG does not have enough sensitivity to put constraints on the potential slope.